Capacity Building and Sustainable Development in Nigerian Universities. - Akani, Christian (Advances in Social Sciences Research Journal, 2017)
Western education was colonial in orientation. It was a veritable channel through which colonial values and colonial-Capitalist economy were transmitted to Nigeria. It was meant to produce middle-level manpower for the Colonial Order. With independence, there was less shift on the colonially – inherited system of education . But by the 1990s, it became clear that this type of education made the recipients more dependent on the society, than on their ability to create value, and unable to confront the challenges of the time. The paper seeks to examine how capacity-building in the universities can enhance sustainable development. This is because development is centered on people, and when they have the capacity and ability to recreate themselves, the quality of their lives overtime will improve. This is a qualitative research, and method of data collection was through primary and secondary sources. These include interviews, group discussions, review of existing literature, magazines and newspapers. It was discovered that the high rate of unemployment is largely because of graduates who do not have the capacity to create value and reproduce themselves productively. They depend more on the society to survive than depending on themselves. Consequently, as the burden on the society begins to deepen, the quality of life correspondingly begins to reduce. We, therefore, recommend that the curriculum of our universities should be overhauled so that its graduates will be self-reliant through entrepreneurial activity, instead of solely depending on the society for sustenance and subsistence.